Dapatkah Media Pembelajaran Android Berbasis Representasi Visual Meningkatkan Kemampuan Representasi Siswa?: Ditinjau dari perspektif sisiwa guru - Delis Amala; Marina Setyarini; Tri Jalmo (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to describe visual representation-based android learning media to improve students' representation abilities based on the views of teachers and students. This research involved 39 science teachers and 181 junior high school students in Lampung province. The method used in this study is a mixed method with an explanatory sequential design in order to obtain quantitative and qualitative data through questionnaires and interviews. The results of the study show that teachers and students have a positive perception of the development of visual representation-based android learning media. This study found the fact that there were several factors that caused teachers not to pay attention to students' representation abilities. The teacher believes that the use of learning media can train students' representation abilities and have an impact on increasing student representation abilities. Â